2023
DOI: 10.1039/d3nr04521h
|View full text |Cite
|
Sign up to set email alerts
|

A comparative investigation of the chemical reduction of graphene oxide for electrical engineering applications

Tomasz Chudziak,
Verónica Montes-García,
Włodzimierz Czepa
et al.

Abstract: The presence of oxygen-containing functional groups on the basal plane and at the edges endows graphene oxide (GO) with an insulating nature, that makes it rather unsuitable for electronical applications....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…These values are similar to those reported in other studies (96–399 m 2 g −1 ). 57,58 However, these values are lower than the theoretical SSA of completely exfoliated and isolated graphene sheets (2630 m 2 g −1 ). 59,60 Nevertheless, the observed increase in the SSA during the reduction process is in good agreement with earlier reports.…”
Section: Resultsmentioning
confidence: 81%
“…These values are similar to those reported in other studies (96–399 m 2 g −1 ). 57,58 However, these values are lower than the theoretical SSA of completely exfoliated and isolated graphene sheets (2630 m 2 g −1 ). 59,60 Nevertheless, the observed increase in the SSA during the reduction process is in good agreement with earlier reports.…”
Section: Resultsmentioning
confidence: 81%
“…In our previous systematic study on thermally reduced GO (TrGO) and CrGO, we have shown that crucial properties such as surface area, porosity, electrical and ionic conductivity, and electrochemical activity significantly affect the electrochemical performance of materials used in ESS. [ 32 ] In the present case, the electrochemical performance of rGOSH electrodes is more than twice the performance of CrGO electrodes, despite the superior electrical conductivity of the latter. While their surface area is comparable, the main differences between the two materials are the higher porosity of rGOSH, together with the nature and amount of active sites, proving that the combination of OFGs and thiol groups is an excellent solution for boosting the electrochemical performance of rGO materials for Zn 2+ ions storage.…”
Section: Resultsmentioning
confidence: 74%
“…The calculated Brunauer–Emmett–Teller (BET) surface area of rGOSH amounts to 78.96 m 2 g −1 , indicating a sixfold increase in the surface area when compared to pristine GO (12.61 m 2 g −1 ) yet being slightly smaller than CrGO (124.92 m 2 g −1 ) (Table S3 , Supporting Information). [ 32 ] Interestingly, the average pore size of rGOSH amounts to 10.2 nm, thus it is nearly twice the one of GO or CrGO. Figure S10 (Supporting Information) shows the differential distribution of pore volumes versus pore sizes for rGOSH, revealing that rGOSH has a predominant mesopore distribution with sizes in the range between 10 and 100 nm.…”
Section: Resultsmentioning
confidence: 99%
“…A well-known method for producing graphene-based materials involves oxidizing graphite powder to produce graphene oxide (GO), which is then chemically reduced to produce reduced graphene oxide (RGO). Hydrazine hydrate, sodium borohydride, sodium hydroxide, sodium dithionite, L-ascorbic acid, and formaldehyde 6 8 all have been employed as reducing agents to produce RGO. RGO represents a class of materials with various physical/chemical properties that vary greatly upon various sources of oxygen-containing groups, including hydroxyl, carboxyl, and epoxy as well as their amount 9 .…”
Section: Introductionmentioning
confidence: 99%